Miniature miracle [videorecording] the computer chip - Jampel, Barbara; Kane, Dennis B.; Skinner, Thomas (National Geographic Society special, 1985)
Documentary about progress in computer technology and its applications to everyday life. The new technological era is a miniature miracle - the computer chip, a power packed chip coupled with human ingenuity.